Aplicação de método geofísico em estudo hidrogeológico, no município de Nova Lima - MG: caracterização de aquíferos em área urbana - Kenia Janete Guerra (2010)
This research was carried out in an 7.000m2 area belonging to Georadar Levantamentos Geofísicos S.A., in Nova Lima county. The investigated area is part of the mineral provinces Quadrilátero Ferrífero, which consists of Archean and Paleoproterozoic rocks, particularly in the Nova Lima group, unit of the Supergroup Rio das Velhas. There are two major lithological units: the talc chlorite schist with quartz sulfide veins, and two smaller fractured itabirite outcrops. In order to characterize the conditions of the aquifers in the investigated area, a set of geophysical and hydrogeological studies has been adopted. First, a preliminary survey to determine the different types of rocks and the water level in the subsurface was carried out by a geophysical method of resistivity (vertical eletrical souding VES). Three monitoring wells and a supply well were drilled and a well-log geophisycal was performed using 4 tools (resistivity, gamma-ray, caliper and optical) in each well. Analysis of geophysical data together with data the litology obtained through the examination of the borehole cuttings data made it possible to identify three aquifer units in the area, the main one being the itabirite fractured aquifer. Two tests for the identification of hydrodynamic conditions of the itabirite fracture aquifer were performed: Bail test in the 3 monitoring wells and a pumping test, the latter showing better results for hydraulic conductivity. A water sample from the itabirite aquifer was collected and chemistry characterized. The results indicate hydraulic conductivity (10-6 m/s) and the presence of chlorinated magnesium water. The analysis of potability indicates good conditions for consumption, except for the high concentrations of antimony and selenium.